Penerapan Etika Bisnis dalam Meningkatkan Penjualan UMKM di Era Digital - Darmawan, Roslinda Jasmine; Rahmatullah, Viko; Dilla, Fara; Dina, Nur (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
The digital era has opened up great opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their markets through digital platforms such as e-commerce and social media. However, this transformation also presents challenges in maintaining business integrity and ethics amidst fierce competition and increasing consumer awareness. This study aims to analyze the application of business ethics in MSME digital practices and its impact on increasing sales. With a literature approach and secondary data analysis from national reports, this study found that the application of ethical principles such as transparency, honesty, and social responsibility has a positive impact on consumer reputation and loyalty, which ultimately improves sales performance. The results of this study are expected to be a strategic reference for MSME actors in developing sustainable and ethical digital businesses.